Understanding mitochondrial biogenesis through energy sensing pathways and its translation in cardio-metabolic health. (27th May 2018) - Nirwane, Abhijit; Majumdar, Anuradha
Abstract: Mitochondria play a pivotal role in physiological energy governance. Mitochondrial biogenesis comprises growth and division of pre-existing mitochondria, triggered by environmental stressors such as endurance exercise, caloric restriction, cold exposure and oxidative stress. For normal physiology, balance between energy intake, storage and expenditure is of utmost important for the coordinated regulation of energy homeostasis. In contrast, abnormalities in these regulations render the individual susceptible to cardiometabolic disorders. This review provides a comprehensive coverage and understanding on mitochondrial biogenesis achieved through energy-sensing pathways. This includes the complex coordination of nuclear, cytosolic and mitochondrial events involving energy sensors, transcription factors, coactivators and regulators. It focuses on the importance of mitochondrial biogenesis in cardiometabolic health. Lastly, converging on the benefits of caloric restriction and endurance exercise in achieving cardiometabolic health.